Situating Open Data: Global Trends in Local Contexts 2020
DOI: 10.47622/978-1-928502-12-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Using open data for public services

Abstract: Chapter 3 in the edited volume Situating Open Data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…These findings support previous research on the improvement of the decision-making process [5,9], the improvement of access to public services [43][44][45], and the development of new processes, products, and services [3,9,46]. These results seem reasonable for the public sector as governments strive to transform operations digitally.…”
Section: Q2 Results and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings support previous research on the improvement of the decision-making process [5,9], the improvement of access to public services [43][44][45], and the development of new processes, products, and services [3,9,46]. These results seem reasonable for the public sector as governments strive to transform operations digitally.…”
Section: Q2 Results and Discussionsupporting
confidence: 87%
“…These results are consistent with previous research that indicated OGD use increases administrative effectiveness and efficiency by implementing evidence-based decision-making processes, reducing work duplication within the government, and improving the access and provision of public services [40,43,45]. Moreover, governments implement OGD initiatives to improve transparency and provide better services for society [5,9,41].…”
Section: Plos Onesupporting
confidence: 91%